The Future of ACP-EU Fisheries Relations: Towards more Sustainability and Improved Social and Economic Well Being for ACP Coastal Communities - Gorez, Beatrice (Technical Centre for Agricultural and Rural Cooperation, 2006)
This publication reviews the main approaches of the players to issues at the top of the ACP-EU fisheries relations agenda...